PENGEMBANGAN MEDIA ANIMASI HURUF UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF ABJAD PADA ANAK KELOMPOK A PAUD AL-KHAIRAT KALUMPANG - Abdullah, Nurhidayati; Sahidun, Nurfitri; Listiawati, Listiawati; Lukman, Sulvianti; sangu, Indriyani; kofia, Sarkia; Ridwan, Fitriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop an animated letter media as a learning tool to improve the ability to recognize alphabet letters among children aged 4–5 years at PAUD Alkhairat Kalumpang. The study employed the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The animated media was designed to suit early childhood characteristics with engaging visuals, bright colors, simple audio, and interactivity. Media validation by experts resulted in an 85% feasibility score (very feasible). Trial results showed a significant improvement in children's letter recognition abilities, from 39.40% (unfeasible) to 71.63% (feasible) after using the media. It also increased children's interest, attention, and engagement in the learning process. The results indicate that the animated letter media is both effective and appropriate to be used as an alternative instructional media for enhancing alphabet recognition among children aged 4–5 years